The practice of customs valuation methods in developing countries - Menciūnienė, Vida; Rugenytė, Daiva; Simanavičienė, Žaneta (Business, Management and Economics Engineering, 2010)
For importers, the process of estimating the value of a product at customs presents problems that can be just as serious as the actual duty rate charged. The WTO agreement on customs valuation aims for a fair, uniform and neutral system for the valuation of goods for customs purposes – a system that conforms to commercial realities, and which outlaws the use of arbitrary or fictitious customs values. According to The World Bank, the lack of understanding of customs valuation and of its supporting procedures are two of the principal factors minimizing the efficiency of the customs administrations in many developing countries. In this context, the aim of this paper is to analyse the problems of customs valuation methods practice in developing countries. Many developing countries face serious difficulties in implementing the ACV.Article in Lithuanian.Importuojamų prekių muitinės vertės nustatymo metodų taikymas besivystančiose šalyse